Nutritional predictors for postoperative short-term and long-term outcomes of patients with gastric cancer. Issue 24 (June 2016) - Kanda, Mitsuro; Mizuno, Akira; Tanaka, Chie; Kobayashi, Daisuke; Fujiwara, Michitaka; Iwata, Naoki; Hayashi, Masamichi; Yamada, Suguru; Nakayama, Goro; Fujii, Tsutomu; Sugimoto, Hiroyuki; Koike, Masahiko; et al.
Abstract : Abstract: Evidence indicates that impaired immunocompetence and nutritional status adversely affect short-term and long-term outcomes of patients with cancer. We aimed to evaluate the clinical significance of preoperative immunocompetence and nutritional status according to Onodera's prognostic nutrition index (PNI) among patients who underwent curative gastrectomy for gastric cancer (GC). This study included 260 patients with stage II/III GC who underwent R0 resection. The predictive values of preoperative nutritional status for postoperative outcome (morbidity and prognosis) were evaluated. Onodera's PNI was calculated as follows: 10 × serum albumin (g/dL) + 0.005 × lymphocyte count (per mm 3 ). The mean preoperative PNI was 47.8. The area under the curve for predicting complications was greater for PNI compared with the serum albumin concentration or lymphocyte count. Multivariate analysis identified preoperative PNI < 47 as an independent predictor of postoperative morbidity. Moreover, patients in the PNI < 47 group experienced significantly shorter overall and disease-free survival compared with those in the PNI ≥ 47 group, notably because of a higher prevalence of hematogenous metastasis as the initial recurrence. Subgroup analysis according to disease stage and postoperative adjuvant treatment revealed that the prognostic significance of PNI was more apparent in patients with stage II GC and in those who received adjuvant chemotherapy. Preoperative PNI is easy and inexpensive to determine, and our findings indicate that PNI served as a significant predictor of postoperative morbidity, prognosis, and recurrence patterns of patients with stage II/III GC.